Pengaruh Kedisiplinan dan Motivasi Belajar Terhadap Prestasi Belajar Matematika Kelas V - Azwar Muamar; Yasin Yasin; Didik Tri Setiyoko (Departement of Mathematics Education, 2023)
Discipline and learning motivation are problems that are often found in the world of education. Discipline and learning motivation is one of the keys that can improve learning achievement in schools. Many students have poor learning achievement, this can be influenced by discipline and lack of student learning motivation, especially in mathematics students often have poor learning achievement. Therefore this study aims to determine the effect of discipline and learning motivation on learning achievement. The time in this study started from February to July 2023. The research location was at Luwunggede 02 Public Elementary School. The population in the study was all fifth grade students and the sample used used a saturated sample, namely the entire population became a sample of 48 students. In this study using multiple regression analysis by conducting a partial test (t-test), simultaneous test (f-test), test the coefficient of determination (r2). The results of this study indicate that 1) There is an influence between discipline on mathematics learning achievement in class V SD Negeri Luwunggede 02. 2) There is an influence between learning motivation on learning achievement in mathematics in class V SD Negeri Luwunggede 02. 3) There is an influence between discipline and learning motivation on the learning achievement of fifth grade mathematics at SD Negeri Luwunggede 02.